As línguas étnicas no Parque das Tribos em Manaus - um estudo etnolinguístico nos espaços culturais indígenas Unka Umbuesara Wakenai Anumarehit e Kokama - Mustafa, Amanda Ramos (2018)
Language, considered a production of humanity and understood as a social practice, enables the subject to construct one`s own trajectory, and transform onesself into a historical and social being. In the context of indigenous populations this condition becomes much more visible, precisely because they are subjects with peculiarities in their historical and cultural sense in the configuration of Brazilian people. The language in this scope, is an inseparable element of their ethnic identity roots. Of the more than 1,500 indigenous languages spoken in Brazilian territory at the time of the arrival of the Portuguese, only about 200 are still spoken and among these, some are threatened with extinction. It is, under this approach, that the present research is developed, whose objective is to register the linguistic teaching practices developed in cultural spaces and the reflections on the uses of ethnic languages in the urban indigenous community of the Parque das Tribos in Manaus. This is an interethnic context, in which about 478 families live, most of them indigenous belonging to 24 different ethnic groups. It is an ethnolinguistic study, which also based on the theoretical assumptions of Sociolinguistics It is characterized as a descriptive and exploratory research, carried out through bibliographical research, field research, through participant observation, using the field diary, questionnaires and interviews.The results indicate that the teaching and social practices of the use of ethnic languages in the Cultural Spaces of Parque das Tribos represents an ascending diacritic that occurs intertwined with the cultural knowledge of the different peoples that live in that locality. Its participants, children, teenagers, young people and adults, acquire ethnic knowledge through a multiple sharing of traditional knowledge and new knowledge. This coexistence environment provides an extension of the linguistic and identity repertoire of its members, strengthens the uses of indigenous languages and multiethnic cultural practices in the everyday life of this large urban indigenous community of Amazonas.